TRADISI NGEMBLOK DI DESA NGREJENG GRABAGAN TUBAN DALAM PERSPEKTIF ‘URF - ., Mun'im; Daud, Fathonah K. (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2022)
This article discusses the Ngemblok Tradition in Ngrejeng Village, Grabagan District, Tuban Regency in the 'Urf. This study aims to: 1) Knowing the Ngemblok tradition in Ngrejeng Village, Grabagan District, Tuban Regency 2) Knowing 'Urf's Review of the Ngemblok Tradition in Ngrejeng Village, Grabagan District, Tuban Regency. This research uses a qualitative case study method and uses data collection methods in the form of observation, interviews and documentation. Then the data analysis techniques used in this research are data reduction, data presentation, conclusion drawing and or verification. The results of this study are'Urf's review of the Ngemblok Tradition in Ngrejeng Village, Grabagan District, Tuban Regency that women as blockers are not prohibited in Islam. This is based on the time of the Prophet Muhammad, who was also proposed by Siti Khatidjah through his trusted female servant, Nafisah. The goal from a religious point of view is to get a husband who is pious, and good for marriage. The legal basis for blocking is on the rules of العادة (‘urf) and the rules of fiqh المحُاَفَظَةُ عَلَى القَدِيْمِ الصَالِحِ الأَخْذُ باِلجَدِيْدِ الأَصْلَحِ (maintaining good old things and taking new, better things).